Impact of Cotton Development Programme on Adoption of Recommended Bt Cotton Cultivation Practices - Singh, Gurdeep; Singh, Pritpal; Sodhi, G. P. S.; Singh, Ranvir; Singh, Kulwant (Indian Journal of Extension Education, 2022)
The study assessed the impact of Cotton Development Programme (CDP) on the adoption of recommended management practices in Bt-cotton (Gossypium hirsutum L). The data was collected from 210 farmers over a period of six years to make quantitative comparison with baseline data collected during the initial three year period (2013-15) from Mansa district of Punjab. The adoption of crop management practices in Bt-cotton in terms of recommended Bt-cotton hybrids, seed rate, fertilizer dose, use pattern of potassium nitrate (KNO3; 13:00:45) and reduction in insecticide use was investigated to quantify the impact of the CDP in the study region. These results revealed that area under recommended Bt cotton hybrids increased from a meager 15.2 per cent to as high as 89 per cent; adoption of recommended use nitrogenous fertilizers increased by 15.1 per cent; and the productivity of Bt-cotton enhanced by 138 per cent during this period. Therefore, it could be concluded that implementation of CDP was successful in the revival of Bt-cotton cultivation which was severely affected due to severe attack of sucking pests particularly by whitefly (Bemisia tabaci) during kharif-2015.
Keywords: Bt-cotton; Adoption; Impact; South-western Punjab